The Readiness of Community Based Tourism: Facing Digitalization on Post-COVID Crisis in Dayu Tourism Village - Hakim, Luqman Al; Sari, Ayu Istiana (Journal of Indonesian Tourism and Development Studies, 2023)
The study aims to investigate the readiness of Community-based Tourism (CBT) in the COVID-19 crisis facing digitalization. The method of the study is a descriptive study. The research subjects are 15 villagers participating in the Dayu tourism village. They are the villagers' representatives who work in tourism during the pandemic and based on permission from the Head of the Village. The research setting is at Dayu tourism village, Gondangrejo, Karanganyar, Central Java. The study was done in September 2021. The data were taken through observation and questionnaires. Data were analyzed through data display, data reduction, and drawing conclusions. The results of the study are (a) less than 30% of the villagers use the Internet, E-mail, Facebook, Instagram, Affiliate Marketing, What's App, Social Media, and Instagram to promote their products and skills; (b) most of them upload their products and skills in the form of a photograph, and less than 50% of them use songs, written form, and videos; (c) Less than 25% of them upload their owned content and their friends' content to social media; (d) there were less than 50% of them who were able to create videos, written form, and movement; and to choose themes Economic, fashion, religion, short movie about local community, promotion, education, social, culture, and arts as their social media content.   Keywords: Community based Tourism, Digitalization, Post-COVID crisis, Social Media.